The neglected sound: music “re-invented”, Luciano Berio Sequenza lll the “antidote” for vocal technique - Mkhwanazi, Fanelesibonge Khozinkosi (College of Music, 2026)
“…but the voice is maybe not an instrument; it is a collection of technical and expressive possibilities that one must discover every time.”1 This paper undertakes the "rediscovery" of the neglected sounds that makes up the “language” of human vocal expression; exploring the barrier between music and sound. By examining the use of Berio's extended techniques in Sequenza III, particularly in terms of vocal application, this paper will assess how the complex use of the voice in a composition like this can benefit the vocal technical element for classical singers. The technical benefits of extended techniques have been somewhat investigated for different reasons. Though the approach that I will follow is taken from the claims of this technical style being a representation of the echo of our ancestors, meaning it's the closest to what “music” must have been for the early humans. And in terms of practical applications, there is a gap in literature, though there are a few suggestions. This paper will also offer a pedagogy approach to putting into effect this approach of bettering vocal technique. The maintenance of vocal technical health is a crucial element in the life of a professional singer, as it can determine whether their career will be long and successful or short and abruptly ended. By evaluating the potential advantages and consequences of studying this type of work, it is possible to identify a counter approach that can enhance the methods that are employed in teaching singers this genre of music, thereby mitigating some of the consequences.